RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF KOMPUTER DAN JARINGAN DASAR SMK - Utari Nur Permadi; Asrul Huda (Universitas Negeri Padang, 2019)
The purpose of this research is to design and build a valid, practical and effective interactive learning media using Macromedia Flash 8 software. This type of research uses the IDI (Instructional Development Institute)model. The research and development step consists of three stages, namely define, develop, and evaluate. Three are 3 research instruments to collect data, namely the validation questionnaire, practicality questionnaire, and effectiveness test. The data analysis technique was performed using the Aiken’s V formula. The results of the design carried out produced an application that could be run on all computers/laptops of each student. Based on the results of research in Computer and Basic Network subjects class X TKJ Vocational High School 5 Padang declared valid with Aiken’s V coefficient value obtained an average value of 0,86 from media experts and 0,82 from material experts. The practicality of the media obtained a value of 85,67% from the teacher and 88% from students in the very practical category. The effectiveness test obtained students’ classical completeness of 86,2% and the average value of the gain score of 0,56 in the medium category. Based on the percentage of students’ classical completeness and the gain score, it can be concluded that this interactive learning media was declared effective. Keywords: Interactive Learning Media, Instructional Development Institute, Aiken’s V.